2019
DOI: 10.1039/c8cp06443a
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the influence of the pore size and surface area of activated carbons on the energy storage of electric double layer capacitors with a new potentially universally applicable capacitor model

Abstract: A new capacitor model that confirms the non-constant capacitive contribution of different pore sizes and provides the possibility of simulating the capacitance values of porous carbons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(72 citation statements)
references
References 63 publications
0
72
0
Order By: Relevance
“…Of course, at this point the defect structures of the electrodes play additional crucial roles in the determination of the whole device performance. [13][14][15] Thus, to avoid low storage of charge capacity one has to nd the best matching of electrolyte ion size and pore size. 16,17 Recent supercapacitor studies of activated carbon electrode can be found elsewhere.…”
Section: Activated Carbon (Ac)mentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, at this point the defect structures of the electrodes play additional crucial roles in the determination of the whole device performance. [13][14][15] Thus, to avoid low storage of charge capacity one has to nd the best matching of electrolyte ion size and pore size. 16,17 Recent supercapacitor studies of activated carbon electrode can be found elsewhere.…”
Section: Activated Carbon (Ac)mentioning
confidence: 99%
“…16,17 Recent supercapacitor studies of activated carbon electrode can be found elsewhere. 15,[18][19][20]…”
Section: Activated Carbon (Ac)mentioning
confidence: 99%
“…AC electrodes porosity is also important in the fabrication of EDLC with larger capacitance. Heimbockel et al [ 25 ] documented that the capacitance improved when the pore size enlarged. AC has reasonable big pore size in the range between 20 and 200 Å.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous metal oxides with high surface area and porosity are excellent candidates for supercapacitor applications because the specific capacitance of an electrode depends on the specific surface area and pore size distribution [61,62]. In addition, they possess pseudo capacitances along with electric double-layer capacitance [63].…”
Section: Oxide Aerogelsmentioning
confidence: 99%